2012
DOI: 10.1039/c2nr31570j
|View full text |Cite
|
Sign up to set email alerts
|

Upconversion nanoparticles for sensitive and in-depth detection of Cu2+ ions

Abstract: Detection of Cu(2+) ions and study of their subcellular distribution in physiological processes are of considerable significance because of their potential environmental and biological applications. Some fluorescence based sensors have been developed for selective detection of Cu(2+) ions, based on organic fluorescent probes that specifically bind to Cu(2+) ions. However, these sensors are not suitable for detection in biological samples due to the short penetration depth of UV/visible light used to excite the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(85 citation statements)
references
References 34 publications
1
83
0
1
Order By: Relevance
“…In this method, CTAB not only acts as a capping and phase-transfer agent, but also as the template for the formation of mesoporous structures in the silica sol-gel reaction. This outstanding work provides a new opportunity to directly coat diverse hydrophobic nanoparticles possessing different compositions, shapes, and sizes with mesoporous silica shells [51,52]. Enlightened by these studies, Lin's group and Shi's group have independently reported the synthesis of uniform and monodisperse UCNPs@mSiO 2 nanocomposites using a one-step sol-gel process [44,45,53,54].…”
Section: One-mentioning
confidence: 94%
“…In this method, CTAB not only acts as a capping and phase-transfer agent, but also as the template for the formation of mesoporous structures in the silica sol-gel reaction. This outstanding work provides a new opportunity to directly coat diverse hydrophobic nanoparticles possessing different compositions, shapes, and sizes with mesoporous silica shells [51,52]. Enlightened by these studies, Lin's group and Shi's group have independently reported the synthesis of uniform and monodisperse UCNPs@mSiO 2 nanocomposites using a one-step sol-gel process [44,45,53,54].…”
Section: One-mentioning
confidence: 94%
“…In particular, it is extremely important to note that the single NIR laser used to excite UCNPs does not co-excite dyes that absorb in the UV/visible regions. In this respect, UCNPs are promising energy donors for LRET based ratiometric nanoprobes which provide built-in correction for environmental effects and permit signal rationing [38,39]. All these favorable advantages make UCNPs particularly attractive for biolabeling and biosensing [40e47].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous reports have revealed the good sensitivity and selectivity of UCL sensors towards various metal ions such as Zn 2+ , 8 Cu 2+ , [14][15][16] Hg 2+ , 17 and Pb 2+ ions. 18 Most strategies were established based on the luminescence resonance energy transfer (LRET) phenomenon, by which metal-responsive dyes played important roles in quenching UCL for ratiometric luminescence sensing while promoting the selectivity.…”
Section: -13mentioning
confidence: 99%
“…-chelating molecules. [14][15][16] Hence, the E-chem technique can help establish a versatile, simple, rapid and sensitive UCL sensor. Apart from being developed as an optical sensor, the CFC-UCNP probe is also promising for UCL/E-chem dual modal sensing because the sensitivity of the E-chem sensing mode is comparable to the UCL sensing at 0.3 V.…”
Section: E-chem Performance and Voltage Effects On The Cfc-ucnp Probementioning
confidence: 99%